Primera muerte súbita cardíaca recuperada con angioplastia primaria en Santa Clara: 20 años después - Moreno-Martínez, Francisco L.; Aladro Miranda, Iguer F. (CorSalud, 2017)
Primera muerte súbita cardíaca recuperada con angioplastia primaria en Santa Clara: 20 años después